Statistics from space: Next-generation agricultural production information for enhanced monitoring of food security in Mozambique - International Food Policy Research Institute (2023)
International Food Policy Research Institute (IFPRI). 2023.Statistics from space: Next-generation agricultural production information for enhanced monitoring of food security in Mozambique. PowerPoint presentation given during the Project Kickoff Meeting (virtual), January 12, 2023.